El teatro y la guerra del Paraguay: ¿Forjando la identidad nacional? - Alicia G. Rubio (Nuevo mundo - Mundos Nuevos, 2009)
According to the outcome of our research, Argentina's theater actors did notshow much interest in the Triple Alliance War. One of the few exceptions is the Spaniard López de Gomara, who arrived to Argentina after the war was over. He wrote a three act play called Curupayty. Performed only once, this work shows the war according to the narratives of Argentinean veterans